2019
DOI: 10.1111/1460-6984.12463
|View full text |Cite
|
Sign up to set email alerts
|

After the RESTART trial: six guidelines for clinical trials of early stuttering intervention

Abstract: Background The Rotterdam Evaluation Study of Stuttering Therapy randomized trial (RESTART) was seminal, comparing the Lidcombe Program with RESTART Demands and Capacities Model‐based treatment (RESTART‐DCM) for pre‐school age children who stutter. Aims To critique the methods of the RESTART trial to develop guidelines for its systematic replication and extension. Beyond that, to contribute to the refinement of existing methodological guidelines for early stuttering intervention. Method The discussion is organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Common responses reported by early childhood professionals during their initial contact with parents who report that their child is stuttering varied between groups. A "wait and see" approach was reported by many public health nurses and preschool teachers while, as expected, very few SLPs reported that they use this approach as current management recommendations advocate for intervention to de delivered as close as possible to stuttering onset (see Onslow & Lowe, 2019). Based on data collected it is unknown what professional's motives for recommending a "wait and see" approach were or how long they recommended this approach for.…”
Section: Responses To Parents During Initial Meetingmentioning
confidence: 95%
See 1 more Smart Citation
“…Common responses reported by early childhood professionals during their initial contact with parents who report that their child is stuttering varied between groups. A "wait and see" approach was reported by many public health nurses and preschool teachers while, as expected, very few SLPs reported that they use this approach as current management recommendations advocate for intervention to de delivered as close as possible to stuttering onset (see Onslow & Lowe, 2019). Based on data collected it is unknown what professional's motives for recommending a "wait and see" approach were or how long they recommended this approach for.…”
Section: Responses To Parents During Initial Meetingmentioning
confidence: 95%
“…For those children who do not recover, early intervention can foster the development of positive communication attitudes and build resilience in CWS against potential negative reactions they may experience from listeners (Byrd & Donaher, 2018;de Sonneville-Koedoot et al, 2015). The promising effectiveness of early intervention coupled with the knowledge that children as young as 3 years of age can be socially and emotionally affected by stuttering (McAllister, 2016) therefore reinforces the critical need for all children to receive effective care as close as possible to stuttering onset (Onslow & Lowe, 2019).…”
Section: Introductionmentioning
confidence: 98%